PTH-111 Improving end of life care for patients with liver disease. (8th June 2018) - Thomson, Sam; Batchelor, Kim; Kriese, Stephen; Ford-Dunn, Suzanne
Abstract : Introduction: Liver disease is the 5th commonest cause of death in the UK and the only major cause of death still increasing. National data show that 73% of deaths occur in hospital and few patients are referred to palliative care services (PC) despite complex symptoms and psychosocial needs. Although preferred place of death for patients with end stage liver disease (ESLD) is unknown, studies of other diagnoses show the majority of patients prefer to die at home, rather than hospital. We aimed to increase access to PC for patients with ESLD and to ascertain preferred place of death. Methods: We commenced a monthly ESLD MDT, comprising Hepatology and PC Consultants, community ESLD Clinical Nurse Specialist (CNS), Alcohol CNS, Social Worker and hospital PC CNS. Patients were identified as outpatients and inpatients and referred to the MDT for discussion. The MDT reviewed patient needs, coordinated care and initiated referrals to additional community services and ESLD CNS. Patients referred to the ESLD CNS received holistic assessment with advanced care planning and contingency plans for future acute decompensation events. Results: In the first 12 months of the new MDT there were 43 deaths with ESLD in our locality, 60% in hospital, 37% in community (home/hospice); contrasting to 73% and 26% nationally. 79% of all patients were known to PC at the time of death. Of 22 patients that expressed a preference for place of death, 11 chose home and 11 hospice; none preferred to die in hospital. Of 22 patients under the ESLD CNS in the community, 73% died out of hospital (7 home, 9 hospice). 68% of patients under the ESLD CNS died in their preferred place of care. Of 26 who died in hospital 30% died on the acute medical unit, HDU or ITU, 30% on the Gastroenterology ward and the remainder (40%) on outlying wards. Conclusions: Most patients with ESLD prefer to die out of hospital, consistent with other terminal illnesses. Although ESLD patients present a challenging symptom burden it appears that an MDT approach including a dedicated CNS can help increase referrals to PC, and help more patients die in their preferred place. However, a third of those dying in hospital did so in an acute environment or while receiving intensive care and therefore were unlikely to have received adequate PC. A notable number also died on non-specialist outlying wards which may imply they too did not receive wholly integrated specialist or PC during their terminal phase. Although the preliminary Results of our local intervention are promising, we recognise that more can still be done and encourage a continued focus on improving end of life support and care planning for patients with ESLD.